THE INFLUENCE OF AFFECTIVE COMMITMENT ON LECTURER PERFOMANCE WITH TALENT MANAGEMENT AS MEDIATOR (Proceeding of SINERGY, 2026)
The workload of lecturers in the areas of teaching, research, community service, and other supporting tasks is considered too high with simultaneous time allocation. This causes fluctuations in lecturer performance, both in terms of quantity and quality. The high or low performance of lecturers is determined by the level of emotional bond between lecturers and the institution, and on how the institution's efforts to improve lecturers' insight and work skills through talent management. This study aims to analyze the direct and indirect effects of affective commitment on lecturer performance through talent management. The sample in this study was 100 lecturers as respondents with a sampling technique using the stratified sampling method. The data analysis technique used was path analysis. The results of the study indicate that affective commitment influences talent management, affective commitment does not affect lecturer performance, talent management influences lecturer performance, and affective commitment influences lecturer performance through talent management. The results of this study indicate that lecturer performance can be improved through improvements and enhancements in affective commitment and talent management.